US immigration authorities collecting DNA information of children in criminal database - Bhuiyan, Johana (The Guardian, 2025)
Collection of migrants’ DNA has increased by 5,000% in three years in a ‘massive expansion of genetic surveillance’
Keywords: Children; Migration; Privacy; Surveillance; Technology; US immigration; US news